Thrombolysis and thrombectomy in patients treated with dabigatran with acute ischemic stroke: Expert opinion. Issue 1 (January 2017) - Diener, HC; Bernstein, R; Butcher, K; Campbell, B; Cloud, G; Davalos, A; Davis, S; Ferro, JM; Grond, M; Krieger, D; Ntaios, G; Slowik, A; et al.
Systemic thrombolysis with rt-PA is contraindicated in patients with acute ischemic stroke anticoagulated with dabigatran. This expert opinion provides guidance on the use of the specific reversal agent idarucizumab followed by rt-PA and/or thrombectomy in patients with ischemic stroke pre-treated with dabigatran. The use of idarucizumab followed by rt-PA is covered by the label of both drugs.